Filantropi Dakwah dan Kaum Minoritas di Indonesia - Okta Nurul Hidayati (Academica: Journal of Multidisciplinary Studies, 2017)
The granting of Islamic philanthropy to Muslim minorities, such as ex-Gafatar, has been practiced by Lazizmu Surabaya. However, such practices are still minimally undertaken by other Islamic philanthropy managers. Many philanthropic practices are aimed at Muslims. This paper wishes to analyze the function of philanthropy for ex-Gafatar members in Indonesia, with a qualitative descriptive method. This paper argues that Islamic philanthropy for ex-Gafatar members not only as a symbol of charity and solving poverty also creates social justice and de-radicalization efforts.Keywords:Islamic Philanthropy, ex-Gafatar, social justice, deradicalization.